2019
DOI: 10.3390/cancers11050704
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and Gap Junctions in Cancer of the Urinary Tract

Abstract: This review focuses on connexins and nexus or gap junctions in the genesis, progression, and therapy of carcinomas of the human urinary tract. Some decades ago, the idea was born that gap junctional intercellular communication might prevent both the onset and the progression of cancer. Later evidence indicated that, on the contrary, synthesis and the presence of connexins as a prerequisite for gap junctional intercellular communication might promote the occurrence of cancer and metastases. The research history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Multiparametric SL-DT assay is suitable for different cell types. To set up the multiparametric SL-DT assay, WB-F344 cell line was employed as one of the most widely used model for the in vitro assessment of GJIC 9,10 . Nevertheless, multiparametric microplate-based SL-DT assay is suitable also for other cell types, as demonstrated in this study.…”
mentioning
confidence: 99%
“…Multiparametric SL-DT assay is suitable for different cell types. To set up the multiparametric SL-DT assay, WB-F344 cell line was employed as one of the most widely used model for the in vitro assessment of GJIC 9,10 . Nevertheless, multiparametric microplate-based SL-DT assay is suitable also for other cell types, as demonstrated in this study.…”
mentioning
confidence: 99%
“…Besides, Bacillus Calmette-Guerin (BCG) was considered as an agonist of TLR2 and TLR4 and has been widely used in intravesical BCa therapy [41]. Connexins is of great importance for gap junctional intercellular communication and might facilitate the occurrence and metastases of cancer [42]. Ai et al [43] revealed that GAP junction protein CX43 could be a promising therapeutic target for BCa.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the last decade, the scientific community’s understanding of Gj and connexins in cancer has grown considerably, and it is now accepted that Gj and connexins have multiple functions in cancer development, from primary tumor growth to metastatic progression [ 12 , 46 , 47 ]. There are many connexins (21 in humans), and they have differential roles in tumor initiation, progression or metastasis [ 12 , 46 , 47 , 48 , 49 , 50 , 51 ]; this review focuses on the role of connexin43 in cancer development.…”
Section: Brief Overview Of the Role Of Connexin43 In Solid Cancer mentioning
confidence: 99%